Biopiracy and the Regulatory Framework for Material Transfer Agreements in Indonesia - Masrur, Devica Rully; Yulia, Yulia; Zainol, Zinatul Ashiqin; Akpoviri, Frank I (LAW REFORM, 2024)
Biopiracy, the misappropriation of biological and genetic resources including the ones related to traditional knowledge, is a major challenge to some of the world’s megadiverse countries. Indonesia has been a major victim of biopiracy, facilitated by the current patent system. This article examines the case of Indonesia, the second richest of the seventeen identified megadiverse countries. The patent system aims to protect the rights of inventors, but the patent system causes injustice in cases of biopiracy. This research aims to analyse the Indonesian government's policies in dealing with biopiracy cases in Indonesia. This research is a normative legal research which uses the approaches of national and international law, biopiracy case, and conceptual. The Indonesian government has changed the patent law to deal with biopiracy cases through Law Number 13 of 2016 concerning Patent disclosure requirements and has also introduced the Material Transfer Agreements (MTAs) in 2009 to address this problem. They can help in controlling access to the country’s resources based on prior informed consent, promoting collaboration between local and foreign researchers, and ensuring benefit-sharing. However, the realization of these objectives may be undermined by the country’s lack of capacity to monitor compliance with the MTA conditions, the inappropriate use of Intellectual property rights (IPRs), and MTA provisions that allow recipients to transfer material and derivatives to third parties without the country’s consent.